2020
DOI: 10.1021/acsenergylett.0c00839
|View full text |Cite
|
Sign up to set email alerts
|

Multisource Vacuum Deposition of Methylammonium-Free Perovskite Solar Cells

Abstract: Halide perovskites of the form ABX 3 have shown outstanding properties for solar cells. The highest reported compositions consist of mixtures of A-site cations methylammonium (MA), formamidinium (FA) and cesium, and X-site iodide and bromide ions, and are produced by solution processing. However, it is unclear whether solution processing will yield sufficient spatial performance uniformity for large-scale photovoltaic modules or compatibility with deposition of multilayered tandem solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 31 publications
5
134
0
Order By: Relevance
“…[9] A few years later, a few groups reported a fully evaporated PSCs based on both nip and pin structure, reaching the PCE around 20%. [33][34][35][36] Very recently, our group also demonstrated the co-evaporated PSCs with a champion PCE of 20.28% for 0.16 cm 2 and 19% for 1 cm 2 and the first co-evaporated PSMs with a PCE of 18.1% over an active area of 21 cm 2 , proving the excellent scalability of co-evaporation methods. [33] These promising results triggered the interest of further studying optimized scaling-up strategy for PSCs with minimum losses of fill factor (FF) and fabricating PSMs with high geometrical fill factor (GFF) to maximize the active areas.…”
Section: Introductionmentioning
confidence: 94%
“…[9] A few years later, a few groups reported a fully evaporated PSCs based on both nip and pin structure, reaching the PCE around 20%. [33][34][35][36] Very recently, our group also demonstrated the co-evaporated PSCs with a champion PCE of 20.28% for 0.16 cm 2 and 19% for 1 cm 2 and the first co-evaporated PSMs with a PCE of 18.1% over an active area of 21 cm 2 , proving the excellent scalability of co-evaporation methods. [33] These promising results triggered the interest of further studying optimized scaling-up strategy for PSCs with minimum losses of fill factor (FF) and fabricating PSMs with high geometrical fill factor (GFF) to maximize the active areas.…”
Section: Introductionmentioning
confidence: 94%
“…Several reports investigated the thermal evaporation of more complex perovskite compositions, such as double [ 99 ] or triple cation, [ 72 ] or more recently the emerging MA‐free perovskites, such as FAPbI 3 [ 100 ] or (Cs,FA)Pb(I,Br) 3 compositions. [ 21,22 ] The efficiency of these devices is <19%, which could originate from various factors. As described earlier, the microstructure of thermally evaporated layers typically consists of smaller, less regular grains, resulting in more grain boundaries and potentially, higher recombination losses.…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…Importantly, unlike solution‐processed perovskite films, it is possible to form crystalline perovskite layers by thermal evaporation without annealing; [ 20 ] however, many studies still rely on annealing for improving the evaporated films’ properties. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Its composition is a very important factor and until recently pure-MA-based perovskites were considered unstable. [14,15] Recently, however, Holzhey et al, demonstrated that solution-processed MAPbI 3 -based solar cells exhibited operational stability in excess of 500 h under illumination when kept at 65 C. [16] It has been found that the residual solvent in the perovskite layer, [17] crystal structure, [18] grain size, [19] defect density, [20,21] and compactness of the film [22] affect the degradation of the perovskite layer. [23] Therefore, the preparation method is an important factor in obtaining stable perovskite films.…”
Section: Introductionmentioning
confidence: 99%